An Updated Classification: Important Branching and Perforator Patterns in Robotic-assisted Deep Inferior Epigastric Artery Perforator Flaps - Suphalerk Lohasammakul, MD; Mandy Flor, MD; Kongkrit Chaiyasate, MD, FACS; Jesse C. Selber, MD, MPH, MHCM, FACS (Plastic and Reconstructive Surgery, Global Open)
Background:. Robotic-assisted deep inferior epigastric artery perforator (DIEP) flap surgery requires specific vascular anatomy for optimal flap harvest. Deep inferior epigastric artery (DIEA) branching patterns were described as follows: single trunk (type 1), bifurcation (type 2), trifurcation (type 3), and 4-branch (type 4) above the arcuate line. This study demonstrated an additional type 5 anatomy—double trunk at the takeoff from the external iliac artery—as well as an updated classification of DIEA dominant perforator patterns. The significance is described. Methods:. A retrospective review of preoperative computed tomographic angiography and intraoperative anatomy of 50 patients who underwent DIEP flap breast reconstruction was performed. A total of 100 DIEAs and their branching and perforator patterns were analyzed. Results:. Out of 100 DIEAs reviewed, there were 59, 34, 4, 1, and 2 classified as types 1, 2, 3, 4, and 5, respectively. Only 1 case with such anatomy contained a dominant perforator that would supply perfusion to the DIEP flap, meaning that in the other case, both arterial trunks were required. The perforator pattern was also described. Conclusions:. DIEA branching and perforator patterns were introduced, including a rare variation in the DIEA’s branching pattern: a double trunk. Importantly, one of these trunks might lack a dominant perforator. To minimize donor site complications and ensure adequate blood flow to the flap, it is crucial to identify this variation and the perforator anatomy using preoperative computed tomographic angiography. Ultimately, whether it involves both trunks or just 1, the correct perforator selection is key.